Implementation Of Accountability And Transparency Towards The Implementation Of The Rice Non-Cash Social Assistance Program In 2023 : Case Study Of Bulak Urban Village In Surabaya City - Al Bira, Ahmad Mubarak; Lating, Ade Irma Suryani; Sidarta, Alphasyah Lazuardy (Universitas Pendidikan Ganesha, 2024)
The study focuses on assessing the accountability and transparency of the implementation of the Rice Non-Cash Social Assistance Program in Bulak Village. The research, utilizing a descriptive qualitative approach in the form of a case study, relies on both primary and secondary data sources. Primary data is gathered through direct interviews, while secondary data is derived from December 2023 records of Rice Non-Cash Social Assistance recipients. Findings reveal that the program's implementation in Bulak Village aligns with accountability and transparency indicators, except for unpredictability in the distribution schedule by BULOG, the supplier. Despite this, the implementation complies with regulations and meets the stipulated accountability and transparency criteria. However, the irregular distribution schedule affects the community negatively. The study recommends consistency in Non-Cash Rice Social Assistance distribution, urging rice providers and local governments to address obstacles by considering additional vendors. Furthermore, maintaining transparent communication with the community regarding the program's implementation is emphasized. In conclusion, the study highlights the overall success of the program with room for improvement in distribution predictability for enhanced community impact.